Prophylactic clipping for the prevention of bleeding following wide-field endoscopic mucosal resection of laterally spreading colorectal lesions: an economic modeling study - Bahin, Farzan F.; Rasouli, Khalid N.; Williams, Stephen J.; Lee, Eric Y. T.; Bourke, Michael J. (Endoscopy, 2016)
Background and study aims: Clinically significant bleeding (CSPEB) is the most common adverse event following endoscopic mucosal resection (EMR) of large sessile and laterally spreading colorectal lesions (LSLs), and is associated with morbidity and resource utilization. CSPEB occurs more frequently with proximal LSLs. Prophylactic clipping of the post-EMR defect may be beneficial in CSPEB prevention. The aim of this study was to determine the cost-effectiveness of a prophylactic clipping strategy. We hypothesized that prophylactic clipping in the proximal colon was cost-effective.Patients and methods: An economic model was applied to outcomes from the Australian Colonic Endoscopic Mucosal Resection (ACE) Study. Clip distances of 3, 5, 8, and 10 mm were analyzed. The cost of treating CSPEB was determined from an independent costing agency. The funds needed to spend (FNS) was the cost incurred in order to prevent one episode of CSPEB. A break-even analysis was performed to determine cost equivalence of the costs of clipping and CSPEB. Results: Outcomes of 1717 LSLs (mean size 35.8 mm; 52.6 % proximal colon) that underwent EMR were analyzed. The overall rate of CSPEB was 6.4 % (proximal 8.9 %; distal 3.7 %). Endoscopic management was required in 45 % of CSPEB episodes. With a clip distance of 3 mm, the expected cost of prophylactic clipping was € 1106 per lesion compared with € 157 per lesion for the expected cost of CSPEB without clipping. At 100 % clipping efficacy, the FNS was € 14 826 (proximal and distal lesions € 9309 and € 29 540, respectively). A clip price of € 10.35 was required for the cost of clipping to offset the cost of CSPEB. Conclusions: A prophylactic clipping strategy is not cost-effective and at present cannot be justified for all lesions or selectively for lesions in the proximal colon.Trial registration: ClinicalTrials.gov (NCT01368289).